2017
DOI: 10.1590/1807-2577.04917
|View full text |Cite
|
Sign up to set email alerts
|

Ultramorphology of pre-treated adhesive interfaces between self-adhesive resin cement and tooth structures

Abstract: Introduction Convencional resin cements can be used in combination with a total-etch system in a conventional mode or as self-adhesive resin cements. The latter are less technique sensitive and able to bond to dental tissues without previous treatment or adhesive layer and requires only a single step to be applied to dental structures. Objective To compare qualitatively the adhesive interfaces of two self-adhesive resin cements and one conventional resin cement after different tooth surface treatments under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
3
0
4
Order By: Relevance
“…Current breakthrough studies demonstrate that the use of buffer systems when forming a hybrid biomimetic layer, including amino acids and alkalis, should contribute to the improved integration of synthetic systems with the dental hard tissue [ 25 , 26 , 27 , 28 ]. The introduction of amino acids and alkalinization under given conditions should increase the hierarchical organization of the pretreated organomineral matrix of apatite [ 8 , 29 , 30 , 31 ]. Thus, in our previous work, it was shown that the pretreatment of enamel in the alkaline solution of Ca(OH) 2 and an amino acid booster, and the following mineralization performed with the use of hydroxyapatite (HAp), resulted in the formation of a mineralized layer with homogeneous micromorphology and presumable orientation of HAp nanocrystals [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current breakthrough studies demonstrate that the use of buffer systems when forming a hybrid biomimetic layer, including amino acids and alkalis, should contribute to the improved integration of synthetic systems with the dental hard tissue [ 25 , 26 , 27 , 28 ]. The introduction of amino acids and alkalinization under given conditions should increase the hierarchical organization of the pretreated organomineral matrix of apatite [ 8 , 29 , 30 , 31 ]. Thus, in our previous work, it was shown that the pretreatment of enamel in the alkaline solution of Ca(OH) 2 and an amino acid booster, and the following mineralization performed with the use of hydroxyapatite (HAp), resulted in the formation of a mineralized layer with homogeneous micromorphology and presumable orientation of HAp nanocrystals [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, numerous studies focus on the interaction of synthetic material with dental tissues as well as formation of a biomimetic buffer layer at the interface between the natural hard dental tissue and the dental composite [2][3][4][5] supposed to act as a link between two heterogeneous materials.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent advances in dental materials science, the cements and filling materials employed to restore the anatomic bases of human teeth or their parts have low affinity for the teeth enamel and dentin [ 1 , 2 ]. As a result, there is poor adhesion and secondary caries most likely to occur at the boundary of dental filling materials and the enamel [ 2 ]. In this regard, improving the integration of applied or developed materials with the dental matrix is a challenge of modern dentistry [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esta capa formada por dentina subyacente contiene restos de colágeno, hidroxiapatita en polvo mezclados con restos contaminantes como saliva, bacterias y otros. 17,29 Se adhiere firmemente y es difícil de remover con aire y/o agua, posee un espesor de 0.5 a 5.0 µm reduciendo la permeabilidad dentinaria hasta en 86%. 17 Si bien es cierto que estos agentes cementantes tienen en su composición monómeros ácidos, estos no son lo suficientemente fuertes para infiltrarse a través del barro dentinario y formar tags de resina.…”
Section: Introductionunclassified
“…Regularmente se utiliza el ácido poliacrilico entre el 10% y el 25% de concentración para modificar o disolver el barro dentinario, limpiar la preparación e impregnan los tejidos, todo esto para mejorar la adhesión del cemento a la dentina. 16,28 El ácido poliacrílico remueve parcialmente el barro dentinario y contaminantes superficiales, cambiando así la energía superficial, 29,30 mejorando la humectabilidad superficial y exponiendo la estructura mineralizada dental para la difusión del ácido de los cementos autoadhesivos mejorando el intercambio iónico. 22,23 El pH en promedio del ácido poliacrílico es de 1.5 a 2 y esto dependerá de la concentración que tenga, a pesar de su naturaleza acida produce una irritación mínima en la pulpa ya que es un ácido de naturaleza débil.…”
Section: Introductionunclassified